Development of a roll-to-roll thermal imprinting system with seamless belt-type template. (23rd June 2017) - Shan, X C; Chen, S H; Mohahidin, M Bin; Wei, J
Abstract: Compared to conventional thermal imprinting using a flat mold, roll-to-roll (R2R) thermal imprinting using a roller mold is a high-speed, high through-put process. In an R2R thermal imprinting process, however, the contact duration between a mold and a thermoplastic substrate is extremely short. This results in insufficient heating and pressing, leading to low fidelity of the imprinted microstructures. We have developed an R2R thermal imprinting system, which allows us to extend the contact duration between the mold and substrate. This system consists of two continuous, seamless belts that are made of metal foil. Each belt is driven by an individual hot roller; at least one belt is used as an imprinting mold, another as a carrier belt. A thermoplastic film to be imprinted is sandwiched between the two belts that provide preheating, heating and pressing, holding, and cooling for demolding during imprinting, leading to extended mold-substrate contact duration and enhanced heat transfer from the belt mold to the polymer film. R2R thermal imprinting has been performed successfully and promising results have been demonstrated.